Ogilvie Syndrome - summary of knowledge, diagnostics and treatment - Radulski, Jakub; Tomkiewicz, Julia; Tomkiewicz, Michał; Olko, Paweł; Rybkowska, Agnieszka; Paluch, Michał; Szczuraszek, Hugo; Bętkowska, Paulina; Licak, Gabriela; Szczuraszek, Paulina (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Ogilvie’s syndrome is an acute pseudo-obstruction of the colon characterized by massive dilatation of the large intestine without mechanical obstruction. The aim of this publication is to review publications and case reports concerning this disease and therapeutic management. A brief description of the state of knowledge: Ogilvie’s syndrome was first described in 1948. The assumed pathogenesis of the disease is increased activity of the sympathetic nervous system and/or decreased activity of the parasympathetic nervous system. Most often it concerns hospitalized patients, in a serious general condition, after major injuries, operations, and pregnant or postpartum women. The importance of viral infections in the pathogenesis, including COVID-19 in recent years, is also indicated. It is important to eliminate possible organic causes of obstruction and to assess the diameter of the dilated bowel. Therapeutic options include conservative treatment, pharmacological treatment with acetylcholinesterase inhibitors, endoscopic bowel decompression and surgical treatment. Lack of medical intervention can lead to ischemia and intestinal perforation. Conclusion: Ogilvie’s syndrome is a rare condition in which complications can be minimized with proper assessment, care and treatment. The progress of pharmacological and endoscopic therapy allows to reduce the need for surgical intervention, and thus - the patient’s unnecessary burden.